Chemical Activation of Bentonite Clay and Its Adsorption Properties of Methylene Blue - Susilawati Susilawati; Nurul Alam Naqiatuddin (Jurnal Natural, 2014)
Study on adsorbent properties of bentonite such as optimum activation condition, concentration concentration effect of sulphuric acid, activation temperature and activation time on decolorization of methylene blue have been investigated in this paper. The study was started by activation of bentonite with sulfuric acid. The data was analysis by statistical method via Least Significant Difference (LSD) test. The optimum condition of adsortion showed that the concentration of activating agent (sulphuric acid) was 20%, activation temperature at 110 ºC and activation time was 30 minutes. At this optimum condition, methylene blue was absorbed by bentonite with 93.30% yield.